Proposta de secagem de transformadores imersos em líquido isolante utilizando óleo vegetal - Fujita, Thais (2014)
This document presents the work of a proposed application of natural ester as a transport agent of water in transformer Off-Line Dry-Out procedures. It shows transformers drying process as a measure of maintenance for preservation and transformer life extensions. Based on that, describes the methodology applied in drying practice using natural ester and mineral oil in a laboratory scale. The laboratory results, presents individual performance of each procedure based on two factors: the water content in the insulating oil and the degree of polymerization on paper.